DEFRAGMENTASI STRUKTUR BERPIKIR SISWA FIELD INDEPENDET DALAM MEMECAHKAN MASALAH GEOMETRI SISWA KELAS VIII SMPN 2 SUMBERGEMPOL - Yuni Alfiatul Husmia (CV. Gerasi Insan Nusantara, 2023)
The background of this study is that there are still many students who have difficulties and errors in solving math problems. The errors faced by students indicate that students have not been able to construct a concept as a whole in solving mathematical problems. This shows that students experience fragmentation of the structure of thinking, namely the delay in the process of constructing concepts and solving mathematical problems due to inefficient storage of information in the brain. Therefore, improving the fragmentation, it can be done by providing defragmentation of the thinking structure, namely the process of restructuring or rearranging the student's thinking structure to reduce the mistakes made. This research used a qualitative approach with a descriptive type. The research location was SMPN 2 Sumbergempol. The researcher took 2 subjects field-independent students. The data collection technique used was the GEFT test (Group Embedded Figures Test), geometry problem-solving tests, interviews, and observations. The data analysis techniques were used data reduction, data presentation, and concluding. The results showed that the students with field-independent cognitive style (FI) in solving geometry problems need defragmentation in the form of improvement of logical thinking structure, improvement of analogical thinking structure, and scheme knitting.